Immunisation status in hospitalised infants: reasons for incomplete immunisation - Othman, Norlijah; B. S., Menon; Mohd Yusof, Azlyna Nur Yanty; S., Noranida (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2005)
Immunisation is known to be an effective health intervention that protects children from infectious diseases. Of all children, infants are most vulnerable if they experience a vaccine preventable disease. The aim of the study was to determine the immunisation status of hospitalised infants, to obtain the reasons of incomplete immunisation and to assess carers’ knowledge on immunisation. Methods: this was a cross- sectional study conducted in the Institute of Paediatrics at Hospital Kuala Lumpur over a 2 month period from June to august 2001. Data were collected through an interview using a structured questionnaire, with the carer of the infant. Questions pertaining to the immunisation status of the infant, reasons of incomplete immunisation and the carer’s knowledge of immunisation were assessed. Results: 115 infants were admitted during the study period; however, only 100 cares of the infant were available for an interview. The average age of the infants was 5.7 months. 22% of the infants had incomplete immunisation. 64% of them had missed more than one vaccine. The commonest missed vaccine was the 3rd dose of diphtheria-pertussistetanus (DOT) and polio vaccine. Reasons of incomplete immunisation include misconception on contraindication of immunisation breakdown with health facilities regarding appointment dates. The under-immunisation rate in the study population was 22%. The under immunisation rate in the study population was 22%. Conclusion: Health providers and the public need to be educated on the importance of immunisation and the associated valid contraindications.